Introdução do pensamento algébrico para alunos do EJA: uma proposta de ensino - Silva, Edgar Alves da (2007)
The aim of this article is to investigate an approach to teach concepts of Unknown, variable and 1st grade equation considering Mathematical Modeling and Etnomathematic studies. The hypotesis was to develop a teaching intervation using problem situations, working the concepts of Unknown, variable and 1st grade equation, contextualized with teens and adults students daily lives. We used 4 teaching intervations in a module IV group (7th and 8th Elementary School grade EJA). The theorical background was based on FREIRE studies associated to freeing education, D´AMBRÓSIO exposures about Etnomathematics theories associated with Mathematical Modeling and the transdiciplinary, SKOVSMOSE highlights of the concepts in Critical Mathematics. Finally, algebraic foundaments and D´AMBRÓSIO considerations about problem solving. Our sample was supposed to do 2 individual tests: one before (pre-test) and another, similar to the first (post-test), after having contact with instruments applied on teaching intervation. In sinthesis, we are able to say that after the teaching intervation and consequently the post-test, students showed a satisfactory performance, higher than the one on the pre-test. We highlight that individual improvement was founded in most students in the reseach. However, our aim was not to generalize these findings to the whole population, once our sample was small. We noticed that the teching and learning process of algeabric concepts is more powerful when it starts from solving a concrete problem which belongs to student s daily lives